Compatibility of tritium permeation barrier coatings with ceramic breeder pebbles. (15th April 2021) - Chikada, Takumi; Kolb, Matthias H.H.; Fujita, Hikari; Nakamura, Kazuki; Kimura, Keisuke; Rasinski, Marcin; Hishinuma, Yoshimitsu; Mukai, Keisuke; Knitter, Regina
Highlights: Cr2 O3 -formed F82H and Er2 O3 coatings were annealed with solid breeder pebbles. Cr2 O3 layer rapidly reacted to form Li2 Fe3 O4, CrFe2 O4, and Cr-O layers at 550 °C. Fe projections generated from Li2 Fe3 O4 layer due to an increase in H2 /H2 O ratio. Er2 O3 coatings did not react with the pebbles at 550 °C but deteriorated at 700 °C. The coating integrity depends on impurity concentrations and coating thickness. Abstract: Reduced activation ferritic/martensitic steel F82H samples with tritium permeation barriers were annealed in contact with ceramic breeder pebbles at 550 °C and 700 °C for up to 32 days under purge gas. Cr2 O3 -formed F82H rapidly reacted to form three layers at 550 °C, and pure Fe projections grew with annealing time. Diffusion kinetics of O and Li were well fitted with Fick's first law of diffusion. Er2 O3 coatings did not react with the pebbles, but deteriorated by oxygen diffusion through the coatings. The impurity concentrations in the system and the coating thickness affect the coating compatibility in solid breeder blanket environments.